Islamic Boarding School: Transformation of the Education System from Traditional to Modern - Ucu Somali; Imam Tabroni; Nur Aisah Jamil (Contemporary Journal of Applied Sciences, 2023)
The Indonesian people realize it or not, there is a dualism in education: General Education and Religious Education. One type of religious education (in this case Islam) is "Pondok Pesantren". Research on the traditionalization and modernization of Miftahul Hidayah Pondok pesantren education uses qualitative methods. Because this research is descriptive in nature, the data are described in their natural state or as they are and the data collected is in the form of words or pictures rather than numbers. The forms of traditionalism that are still maintained by the Miftahul Hidayah Pondok pesantren are the application of the sorogan method, and the recitation of wetonan and halaqoh. The form of modernization absorbed by the Miftahul Hidayah Pondok pesantren through several things, namely teaching methods, the form of the Pondok pesantren building and the Pondok pesantren curriculum. While the traditional systems that are still being preserved are the wetonan and sorogan systems which still use the yellow book and the respect for the kyai and their ustadz is so strong